An Adaptable and Dynamically Porous Organic Salt Traps Unique Tetrahalide Dianions1. Issue 50 (7th November 2013) - Martí‐Rujas, Javier; Meazza, Lorenzo; Lim, Gin Keat; Terraneo, Giancarlo; Pilati, Tullio; Harris, Kenneth D. M.; Metrangolo, Pierangelo; Resnati, Giuseppe
<x xml:space="preserve">Abstract</x> Bis(I2) adducts of hexamethonium dihalides are pre‐organized to respond dynamically to heating and reach a functional structure that favors the formation of the poorly stable and virtually unknown [I2Br2]2− and [I2Cl2]2− tetrahalides which could not be obtained in solution (see picture). The cavity‐directed reactivity affords new opportunities for synthesis and interconversion of polyhalogen anions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>